Faculty wide curriculum reform: the integrated engineering programme. (2nd January 2021) - Mitchell, John E.; Nyamapfene, Abel; Roach, Kate; Tilley, Emanuela
ABSTRACT: Many traditional engineering schools are struggling to balance the calls to provide an innovative engineering education that meet the demands of graduates and their employers with the constraints and momentum of their existing curriculum. In this paper we present the conceptual design behind a framework that integrates existing discipline-specific content with threads of professional skills and design through a backbone of problem-based learning experiences. This framework creates a student-centred pedagogy that has been implemented across eight departments of a large engineering school in a research-intensive university.